Can suitability indices predict plant growth in the invaded range? The case of Acacias species - Silva, Carmen P.; López, Daniela N.; Naulin, Paulette I.; Estay, Sergio A. (Frontiers in Plant Science, 2023)
Forestry in many parts of the world depends on exotic species, making this industry a source of invasions in some countries. Among others, plantations of the genus Pinus, Eucalyptus, Acacia, Populus, and Pseudotsuga underpin the forestry industry and are a vital component of many countries economies. Among woody plants, the cosmopolitan genus Acacia includes some of the most commonly planted trees worldwide. In order to prevent, manage and control invasive plant species, one of the most used tools is species distribution models. The output of these models can also be used to obtain information about population characteristics, such as spatial abundance patterns or species performance. Although ecological theory suggests a direct link between fitness and suitability, this link is often absent. The reasons behind the lack of this relationship are multiple. Chile is one of the countries where Acacia species, in particular, A. dealbata and A. melanoxylon, have become invaders. Here, we used climatic and edaphic variables to predict the potentially suitable habitats for A. dealbata and A. melanoxylon in continental Chile and evaluate if the suitability indices obtained from these models are associated with the observed performance of the trees along the country. Our models show that variable importance showed significant similarities between the variables that characterize each species’ niche. However, despite the high accuracy of our models, we did not observe an association between suitability and tree growth. This disconnection between suitability and performance can result from multiple causes, from structural limitations, like the lack of biotic interactions in the models, to methodological issues, like the usefulness of the performance metric used. Whatever the scenario, our results suggest that plans to control invasive species should be cautious in assuming this relationship in their design and consider other indicators such as species establishment success.